2021
DOI: 10.1371/journal.pone.0252471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of number of individuals and observations per individual on a model of community structure

Abstract: Social network analysis is increasingly applied to understand animal groups. However, it is rarely feasible to observe every interaction among all individuals in natural populations. Studies have assessed how missing information affects estimates of individual network positions, but less attention has been paid to metrics that characterize overall network structure such as modularity, clustering coefficient, and density. In cases such as groups displaying fission-fusion dynamics, where subgroups break apart an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Several studies have suggested that social networks are quite robust to sampling subsets of the population—Silk et al (2015) estimated that studies sampling 30% or more of a population can generate reliable estimates of individuals' social network positions—so GPS devices can theoretically be deployed to characterize even large social networks. Subsequent studies highlighted that repeated sampling and avoiding misidentifications are critical for producing accurate networks (Davis et al, 2018; Sunga et al, 2021)—both are the strengths of GPS tracking data. However, GPS positions are also prone to error and sampling discontinuity (i.e.…”
Section: Social Network Structuresmentioning
confidence: 99%
“…Several studies have suggested that social networks are quite robust to sampling subsets of the population—Silk et al (2015) estimated that studies sampling 30% or more of a population can generate reliable estimates of individuals' social network positions—so GPS devices can theoretically be deployed to characterize even large social networks. Subsequent studies highlighted that repeated sampling and avoiding misidentifications are critical for producing accurate networks (Davis et al, 2018; Sunga et al, 2021)—both are the strengths of GPS tracking data. However, GPS positions are also prone to error and sampling discontinuity (i.e.…”
Section: Social Network Structuresmentioning
confidence: 99%
“…Several studies have suggested that social networks are quite robust to sampling subsets of the population- Silk et al (2015) estimated that studies sampling 30% or more of a population can generate reliable estimates of individuals' social network positions-so GPS devices can theoretically be deployed to characterize even large social networks. Subsequent studies highlighted that repeated sampling and avoiding misidentifications are critical for producing accurate networks (Davis, Crofoot & Farine 2018;Sunga, Webber & Broders 2021)-both are the strengths of GPS tracking data. However, GPS positions are also prone to error and sampling discontinuity (i.e.…”
Section: Social Network Structuresmentioning
confidence: 99%
“…1), this was only a partial focus of our results. Animal social systems vary widely, and while sampling effects optimal sampling strategies are likely to vary with social structure (Clements et al, 2022;Silk, 2018;Sunga et al, 2021), this has remained understudied. Similarly, while we varied network dynamics in our simulations, the network of every individual was drawn from the same probability distribution.…”
Section: Future Stepsmentioning
confidence: 99%